2014
DOI: 10.1002/elsc.201400057
|View full text |Cite
|
Sign up to set email alerts
|

Far‐red light (720 or 740 nm) improves growth and changes the chemical composition of Chlorella vulgaris

Abstract: Research ArticleFar-red light (720 or 740 nm) improves growth and changes the chemical composition of Chlorella vulgaris Far-red (FR) light is crucial for the efficiency of photosynthesis and photomorphogenetic activity. This study investigated whether FR light at different wavelengths affects the Chlorella vulgaris biomass growth rate and chemical composition. For this purpose, FR was added to the blue-red (R) light at the wavelength of 720 nm (BRFR 720 L [blue + R + FR 720 nm light]) or 740 nm (BRFR 740 L [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 24 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…, in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so‐called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…, in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so‐called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture .…”
Section: Resultssupporting
confidence: 85%
“…According to Lang et al [41], in terrestrial plants, several cinnamic acids (ferulic, sinapsis, and caffeic acid) are responsible for the so-called F450, whereas the F530 is attributed to compounds such as berberine, quercetin, and riboflavin. Similar shifts in the fluorescence spectra, suggesting changes in the composition of phenolic compounds, were observed previously during the growth of Chlorella vulgaris culture [34,42]. Fluorescence emission spectra can produce many relevant information regarding plant responses to changing growth conditions, for example, the intensity and/or spectrum of light, temperature, and nutrient deficiency.…”
Section: Phenol Content and Blue-green Fluorescence Emission Spectrasupporting
confidence: 70%
“…Previous studies have revealed that light of different wavelength spectra have various effects on plant growth. For example, blue light (400‐500 nm) mainly contributes to photosynthesis, red light (620‐690 nm) is responsible for phototropism, and far‐red light (700‐740 nm) dominates the process of photo morphogenesis . One of the critical steps of indoor plant cultivation is to find reliable light sources which can provide tunable light spectrum to fit different plant photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, indoor cultivation has attracted considerable attentions over traditional farming mode due to its distinct merits such as high crop yield and stable growth environment . Artificial lights, such as phosphor‐converted light‐emitting diodes (pc‐LEDs), gas discharge lamps (GDLs), and especially fluorescent lamps, play an important role in this advanced technology . Typically, the absorption area of plant pigments can be subdivided into two parts: the bluish violet and red‐far red lights.…”
Section: Introductionmentioning
confidence: 99%